The Position of the General Chapters of the Dominican Brothers Towards the Teaching of St. Thomas Aquinas and the Question of Immaculate Conception - Nawracała, Tomasz (Verbum Vitae, 2024)
The doctrine of Thomas Aquinas was formally adopted as the official teaching of the entire Dominican Order. Throughout the 13th and 14th centuries, general chapters placed significant emphasis on the importance of adhering to Aquinas’ views. They were deemed essential not only to maintain continuity within the orthodox tradition of the Church but also to foster unity within the entire order. Among the topics that sparked debate among medieval theologians was the conception of Mary. While Bernard of Clairvaux and the Dominicans rejected the idea of Mary’s immaculate conception, the Franciscans, led by figures like John Duns Scotus, advocated for it. This article highlights the stance taken by the Dominican general chapters in defence of Thomas’ views. Initially, in the 14th century, there were general indications supporting the maculistic understanding of Mary’s conception, but this stance shifted over time. By the 15th century, the Dominicans were compelled to embrace the immaculistic concept. The delayed promulgation of the dogma of the Immaculate Conception of Mary in the mid-19th century underscores the complexity and unresolved nature of theological discussions throughout the medieval period.